THE ROLE OF LEADERSHIP SKILLS IN THE SUCCESS OF SPORTS CLUBS FROM THE PERSPECTIVE OF CLUB ADMINISTRATORS IN THE NORTHERN GOVERNORATES OF IRAQ - Ola Sabri Hazim (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Leadership is a crucial factor and an effective tool for achieving the goals of any institution, whether it is in the fields of education, the military, economics, politics, or sports. Its significance stems from its role in fostering group cohesion, organizing day-to-day activities, shaping the future, and enhancing overall performance, all while contributing to society. Leadership guides individuals' behavior toward accomplishing specific objectives. The importance of this research lies in its thorough examination of the significance of leadership skills for sports club administrators. It provides valuable insights for those interested in these aspects. To successfully manage the affairs of sports clubs, it is essential to adopt key leadership skills that align closely with achieving goals. This approach advances the administrative process and contributes to accomplishments that keep pace with global progress. The core problem addressed in this research is to evaluate the importance of these leadership skills within sports clubs in the northern region of Iraq, as perceived by the administrators of these clubs. The researcher aims to develop a leadership skills scale specifically for sports club administrators in the northern governorates of Iraq, as well as to assess the importance of these leadership skills in that context. To tackle this issue, the researcher employed a descriptive approach using a survey method. The study's population consists of sports club administrators from the northern governorates, including Kirkuk, Sulaymaniyah, Erbil, and Dohuk, amounting to a total of 342 administrators. The researcher reached technical skills are the most essential leadership skills. Among club administrators in sports clubs, communication is the least utilized leadership skill. In the northern region’s clubs, the ranking of leadership skills possessed by members of the administrative bodies is as follows: human skills, mental skills, and technical skills. In light of these conclusions, the researcher recommends implementing a standardized assessment for leadership skills among sports club administrators. Offering administrative training courses to help sports club administrators advance to higher positions. Prioritizing the development of leadership skills, particularly in the areas of human resources and communication, which were identified as the weakest.